2020
DOI: 10.26457/recein.v14i53.2663
|View full text |Cite
|
Sign up to set email alerts
|

Respuesta inicial por un grupo de docentes mexicanos al cierre escuelas por Covid-19.

Abstract: El presente trabajo tiene por objetivo analizar el actuar de los docentes frente a la suspensión de clases presenciales debido a la contingencia sanitaria provocada por el COVID-19. Se distribuyó un cuestionario con el modelo de Bola de nieve. La encuesta se realizó en fechas previas al anuncio de las estrategias nacionales y las medidas que las instituciones educativas debían tomar. Lo anterior con la finalidad de analizar las acciones realizadas por los maestros para continuar con la actividad académi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Given the strong inequality differences, whereas some public and private education centres made use of learning platforms, in other disadvantaged communities, smartphones were the only digital resource to continue student learning and messaging apps served as a communication tool between students, parents and teachers. Nevertheless, Magallanes Ulloa et al (2020) revealed that nearly 80% of students did not have access to technology. Consequently, teachers could not support all of their students, particularly disadvantaged learners or those attending rural schools (Cárdenas et al, 2022).…”
Section: The Mexican Contextmentioning
confidence: 99%
“…Given the strong inequality differences, whereas some public and private education centres made use of learning platforms, in other disadvantaged communities, smartphones were the only digital resource to continue student learning and messaging apps served as a communication tool between students, parents and teachers. Nevertheless, Magallanes Ulloa et al (2020) revealed that nearly 80% of students did not have access to technology. Consequently, teachers could not support all of their students, particularly disadvantaged learners or those attending rural schools (Cárdenas et al, 2022).…”
Section: The Mexican Contextmentioning
confidence: 99%